Combined influence of organo-modified Indian bentonite nanoclay and fire retardants on thermal and fire behavior of vinylester. Issue 1 (March 2017) - Raghavendra, N; Murthy, HN Narasimha; Firdosh, Salim; Sridhar, R; Angadi, Gangadhar; Mahesh, KR Vishnu; Krishna, M
This article reports synergetic effect of naturally available Indian bentonite nanoclay and fire retardants on the thermal and fire retardation behavior of vinylester. Indian bentonite nanoclay organically modified with hexadecyltrimethylammonium bromide by cation exchange capacity method, along with aluminum trihydroxide and magnesium hydroxide were dispersed in vinylester and tested. Addition of 30% aluminum trihydroxide and 4 wt% Indian bentonite increased the glass transition temperature of vinylester by 24.4%; decreased thermal degradation by 47%, vertical burning rate by 54% and horizontal burning rate by 72%; and increased limiting oxygen index by 56.6% and microhardness by 49.6%.